User interfaces design for collaborative virtual environment (CVE) software / Mohd Kamal Othman - Othman, Mohd Kamal (2006)
The project aims to study and design alternative user interface for Collaborative Virtual Environments (CVE's) software also known as Networked Virtual Environments (NVE's). To reduce cost, most current and operative CVE's use the Internet and standard PC to create a visual Virtual Environment (VE), which can be shared by a large number of users. This project also involves an image processing technique (morphing technique using Thin Plate Spline) for creating a facial expression for the CVE software and OpenGL API for implementation. It discusses communication aspects in the CVE System and proposes the different types of communication that are suitable for the project. It also suggests a suitable user interfaces for the software.